The Impact of Night Entertainment Venues on Transvestite Behavior in Kupang City - Maria Elfira; Balkis Soraya Tanof (Jurnal Pluralis, 2024)
Transvestites visiting THM Dancing Hall can be said to be a form of expression that is constrained by the assumption of a society that marginalises waria due to differences in sexual orientation. At THM Dancing Hall, the transgender community gets more freedom of expression and creativity, release fatigue, and make friends who do not marginalise them because of differences in sexual orientation, because it can be said that most of those who visit THM Dancing Hall come from fellow transgender communities or people with heterosexual sexual orientation (different sex orientation) who consider transgender people visiting THM Dancing Hall as a common thing in nightlife places. The problem in this study is how is the impact of night entertainment venues on the behaviour of transvestites in the Dancing Hall nightlife venue in Flobamora Mall? The subjects in this study were transvestites who were in the Dancing Hall Flobamora Mall with the sampling technique using Snow Ball Sampling Technique. The research findings are that the positive impact is THM as a means of entertainment, THM as a means of expression and THM as a means of interaction. The negative impacts are promiscuity, and sexual deviance.